E-Recrutment Sistem Pendukung Keputusan Penerimaan Pegawai BMT NU Cabang Gayam dengan Metode Simple Additive Weighting - Khairul Anam; Adi Susanto; Achmad Baijuri (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2025)
In today's digital era, the employee recruitment process which is still carried out manually and subjectively is a challenge for companies, including Islamic microfinance institutions such as BMT NU Gayam Branch. A personal approach in employee selection often results in decisions that are less precise and not based on measurable criteria. To overcome this problem, this study aims to design a web-based Decision Support System (DSS) that can help the selection process for new prospective employees objectively and efficiently. This system utilizes the Simple Additive Weighting (SAW) method combined with criteria weighting using the Analytical Hierarchy Process (AHP) method. The research process was carried out using a qualitative approach, through observation, interviews, and documentation studies. Meanwhile, the system development method used is the Waterfall model, which consists of the stages of needs analysis, design, implementation, testing, and maintenance. The results of this study indicate that the application of DSS with the SAW-AHP method can improve selection accuracy, accelerate decision, making, and reduce the influence of subjectivity in the assessment of prospective employees. With this system, BMT NU Gayam Branch is expected to obtain human resources that are more in line with the needs of the organization.